Rectosigmoid prolapse-case report of an uncommon medical condition - Jeremic, Vasilije; Alempijevic, Tamara; Mijatovic, Srdjan; Krstic, Slobodan; Dragasevic, Sanja (Vojnosanitetski pregled, 2016)
Introduction: rectal prolapse (RP) occurs when a mucosal or full-thickness layer of rectal tissue protrudes through the anal orifice. Many factors have been indentified  as a possible cause of RP, such as increase of intraabdominal preasure, weak anal sphincter and malnutrition. Despite the fact that it is not a life-threating condition, the clinical presentation various, and sometimes it can present as an emergency.The objective of this paper is to present a case with prolpase od an unusual large segment of the rectosygmoid colon  caused by chronic constipation and  repaired by an  abdominal approach which included suture rectopexy in conjuction with sigmoid resection due to the magnitude of  the prolaps.Case report: We present a case of a 62 years old female patient, with a prolapse of the complete rectum and a part of sigmoid colon that appeared edematous, livid, with ulcerations. An attempt at manual reduction of prolapse failed, therefor  the  resection of 50cm of sigmoid colon with rectopexy had to be performed.Conclusion: Despite well known etiology, pathophysiology and methods of surgical treatment, rectal prolapse remains a highly controversial disabling medical condition. Surgical repair is the strategy of choice, but well-timed diagnosis enable using less invasive procedure.Although the preoperative management is limited, emergancy surgical intervention for such cases due  to magnitude of  the prolapse provides a successful and permenant solution.